Le radici livornesi ebraiche di Lamberto Borghi - Gaudio, Angelo (Studi sulla Formazione/Open Journal of Education, 2024)
The article presents some notes taken on the biography of Lamberto Borghi regarding Livorno Judaism during the early twentieth century, which is characterized by significant figures in the cultural and political life of the city.